PENGEMBANGAN PROGRAM MEMBACA DI PERPUSTAKAAN: SALAH SATU KOMPONEN PENTING MENJADI MURID MELEK INFORMASI (INFORMATION LITERATE STUDENT)) - Susanti Agustina (Universitas Padjadjaran, 2013)
Learning library as the implementation of user education programs. Elementary school, school to school instead of working. Because students will go to school, then it should have the power to learn good. Before the entrance pupil at the level of information literacy, fundamental thing that is important implanted student interests and reading culture since the early entry into the system. The school library should be made good. Furthermore, to form a good reading habit can through the library learning program called